Art since 1989 254 illustrations - Grovier, Kelly 1968- (World of art, 2015)
The years since the collapse of the Berlin Wall in November 1989 have seen the rise of a new freedom to define art--Who makes it? Where can it be found? What is its commercial value?--and, consequently, the reevaluation of art's place in society. Kelly Grovier surveys the dynamic developments in art practice worldwide since 1989, focusing on artists whose fresh visual vocabulary and innovation reflect these past turbulent decades. The book's ten chapters examine the key themes in contemporary art--portraiture in the age of face transplants and facial recognition software, political activism, science, and religion, to name a few--by artists including Jeff Koons, Louise Bourgeois, Damien Hirst, George Condo, Marlene Dumas, Sean Scully, Cindy Sherman, Banksy, Ai Weiwei, Antony Gormley, Christo and Jean-Claude, Jenny Holzer, Chuck Close, and Cornelia Parker. A chapter-length timeline at the end of the book traces the evolution of art from 1989 to today by closely examining one key artwork from each year